Uji Fungsionalitas Dan Kebermanfaatan Aplikasi Random Angka Soal Vektor Berbasis Web Sebagai Media Latihan Soal - Yunita Citra Dewi; Muhammad Rizqi Sholahuddin; Topan Trianto (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2025)
The fundamental role of vector concepts in engineering education underscores the development of a web-based application designed to facilitate vector problem-solving practice. To enhance students’ comprehension of vector material, repeated exposure to varied problem sets is essential. This study aims to design and evaluate a practice application that integrates randomized number generation, enabling users to encounter dynamically changing numerical values with each use. Employing a Research and Development (R&D) approach with experimental methods, the application was developed using the Laravel Model-View-Controller (MVC) framework. The database structure, built on MariaDB, was optimized for efficient storage of questions, solutions, and user responses. The application was implemented and tested by first-year students in the Diploma 3 Mechanical Engineering Program at Politeknik Negeri Bandung. Functional testing revealed that 92.89% of the features operated effectively. Furthermore, based on the usefulness assessment, the application received a total score of 254, classifying it as “highly useful.”